(untitled) (ModaPalavra e-periódico, 2009)
The study addresses the practical activities on conservation and restoration of textiles materials in institutions in which memory is preserved. The discussion reviews the infrastructure, methods, materials and treatments essential to the conservation and restoration activities in textiles support. Our approach focuses on the Center of Arts, at University of Santa Catarina State, where we could analyze the conservation status of a dress dating from 1910, investigate the factors and types of degradation that changed its structure associated with inappropriate care in use, packaging and storage. The study also describes used treatments to restore the dress and reestablish its physical and functional integrity.